2020
DOI: 10.17645/pag.v8i1.2539
|View full text |Cite
|
Sign up to set email alerts
|

Veridiction and Leadership in Transnational Populism: The Case of DiEM25

Abstract: While research tends to explore questions of power and leadership at the national level, populism in Europe has moved beyond national borders, with an increasing number of transnational movements and organizations. This article investigates the Democracy in Europe Movement 2025 (DiEM25) and its leadership’s main speeches. Informed by both discourse theory and Michel Foucault’s work on parrhesia (veridiction), the analysis draws on readings of transnational Euroalternativism and populism, pointing out the confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…While this article was only able to examine one transnational coalition, the European anti-austerity movement brought forth various others as well, including 'Blockupy' and the 'Alter Summit', whose ambitions towards 'building democracy from below' (Blockupy 2014) and creating a 'united movement for a democratic, social, ecological and feminist Europe' (Alter Summit 2013) speak to their own aspirations for transnational counter-hegemonic leadership. At the same time, the emergence of DiEM25 has shown that it is possible for a more cohesive and centralised activist organisation to facilitate transnational democratic participation and even compete in the European elections (Fanoulis & Guerra 2020), hinting at the possibility of transnational counter-hegemonic leadership more in line with Gramsci's democratic centralist 'modern prince'. These projects offer a wide selection of empirical cases whose contributions to hegemony struggles merit investigation and whose variety underlines again why we should apply the concept of collective intellectual in a more open fashion to capture their innovative strategies and assess how they differ from what we have seen in the past.…”
Section: Discussionmentioning
confidence: 99%
“…While this article was only able to examine one transnational coalition, the European anti-austerity movement brought forth various others as well, including 'Blockupy' and the 'Alter Summit', whose ambitions towards 'building democracy from below' (Blockupy 2014) and creating a 'united movement for a democratic, social, ecological and feminist Europe' (Alter Summit 2013) speak to their own aspirations for transnational counter-hegemonic leadership. At the same time, the emergence of DiEM25 has shown that it is possible for a more cohesive and centralised activist organisation to facilitate transnational democratic participation and even compete in the European elections (Fanoulis & Guerra 2020), hinting at the possibility of transnational counter-hegemonic leadership more in line with Gramsci's democratic centralist 'modern prince'. These projects offer a wide selection of empirical cases whose contributions to hegemony struggles merit investigation and whose variety underlines again why we should apply the concept of collective intellectual in a more open fashion to capture their innovative strategies and assess how they differ from what we have seen in the past.…”
Section: Discussionmentioning
confidence: 99%
“…They ask whether the movement's leadership has succeeded in constructing a transnational "people" by promoting its Euroalternative discourse. Focusing on leader Yanis Varoufakis's veridiction (or truth-telling) speech and agency, the authors conclude that while Euroalternativism has been successful in capitalizing on transnationalism, the spread of populism can be limited by national borders (Fanoulis & Guerra, 2020).…”
Section: Leadership and Populism In European Case Studies Or In Crosmentioning
confidence: 99%
“…).The fourth and most clearly articulated case of transnational populism to have emerged in recent years is DiEM25, the 'Democracy in Europe Movement 2025' led by former Greek finance minister, YanisVaroufakis (see De Cleen et al, 2020;Fanoulis and Guerra, 2020). Launched in early 2016, DiEM25 set out to 'democratise Europe' to save it from disintegration.…”
mentioning
confidence: 99%